VITALITE Zambia Ltd : the intersection of solar energy technology and mobile money in Zambia (case B) - Munthali, Peter; Boyd, Sarah, active 2018; Hamann, Ralph (London : Graduate School of Business, University of Cape Town, 2018)
Case B follows up with VITALITE two years after VITALITE (A), in November 2017, to see how the company has addressed its challenges with business model innovation. The case presents the process of this innovation from the ideation phase through to implementation, the products of which are namely mobile money integration, a customer awareness strategy, and a new partner-enabled offering called "Agri Solutions". Readers will find that there is added emphasis on the need for financial innovation in the solutions presented here, which is indicative of the systemic nature of social enterprise work and private industry in general, in emerging markets. As a more explanatory case, case B allows students to compare their analysis and recommendations with the actual decisions taken by the company to enhance their learnings in BoP strategy and gain exposure to real-world examples of business model innovation in a social enterprise environment.
Originally Published InMunthalia, P., Boyd, S., & Hamann, R. (2018). VITALITE Zambia Ltd: The intersection of solar energy technology and mobile money in Zambia (case B). 2018-15B. Cape Town, South Africa: Graduate School of Business, University of Cape Town.
Description based on XML content.
Keywords: elektronické knihy; electronic books; VITALITE Ltd -- Case studies; New business enterprises -- Zambia -- Management -- Case studies; Solar energy industries -- Zambia -- Case studies